Highly conductive copper films prepared by multilayer sintering of nanoparticles synthesized via arc discharge. (14th March 2023) - Fu, Qingqing; Li, Wen; Kruis, Frank Einar
Abstract: The major challenges in producing highly electrically conductive copper films are the oxide content and the porosity of the sintered films. This study developed a multilayer sintering method to remove the copper oxides and reduce copper film porosity. We used a self-built arc discharge reactor to produce copper nanoparticles. Copper nanoparticles produced by arc discharge synthesis have many advantages, such as low cost and a high production rate. Conductive inks were prepared from copper nanoparticles to obtain thin copper films on glass substrates. As demonstrated by scanning electron microscopy analyses and electrical resistivity measurements, the copper film porosity and electrical resistivity cannot be significantly reduced by prolonged sintering time or increasing single film thickness. Instead, by applying the multilayer sintering method, where the coating and sintering process was repeated up to four times in this study, the porosity of copper films could be effectively reduced from 33.6% after one-layer sintering to 3.7% after four-layer sintering. Copper films with an electrical resistivity of 3.49 ± 0.35 μ Ω·cm (two times of the bulk copper) have been achieved after four-layer sintering, while one-layer sintered copper films were measured to possess resistivity of 11.17 ± 2.17 μ Ω·cm.